Knowledge and practices of self-medication among adolescents - Gabriel, Dimple C.; Balakrishna, Bhavani Bangarkodi (International Journal of Contemporary Pediatrics, 2021)
Background: Self-medication begins in early adolescence, often during the middle school years. By the age of 16, nearly all adolescents have taken medicine independently for minor illnesses and become more involved with managing chronic conditions. Taking medications without a doctor's prescription, even if the ailment is minor, can have serious repercussions. A large number of potent drugs such as pain relievers, cough remedies, anti-allergies, laxatives, antibiotics, antacids and vitamins are sold over-the-counter (OTC). The present study aimed to assess “the knowledge and practices of self-medication among adolescents in selected colleges, Bengaluru, India with a view to develop an informational booklet. Methods: The study was done using a survey design. Simple random sampling technique was adopted to select 100 adolescents from a pre-university college. A socio demographic Performa, a self-reported structured questionnaire to assess knowledge and practice checklist regarding self-medication was used to collect the data. Descriptive and inferential statistics was used for analysis. Results: Self-medication use was reported by 94% of the adolescents. Analgesics 65%, antipyretics 51%, cough and cold medications 49%, vitamins 35%, antibiotics 26%, and antacids 19%, were cited as the most common types of medication taken. Around 45% adolescents had poor knowledge about self-medication. There was a low negative correlation between knowledge and practice of self-medication among participants. (Pearson’s r=-0.44). Conclusions: The practice of self-medication among adolescent was very high. A significant number of adolescents had inadequate knowledge regarding self-medication and its consequences. Therefore, potential problems of self-medication should be emphasised to the adolescents. Need based information booklet was prepared and disseminated to the adolescents.